Two periods of processing in the (circum)striate visual cortex as revealed by transcranial magnetic stimulation. - Corthout, E; Uttl, B; Ziemann, U; Cowey, A; Hallett, M (1999)
To determine the timing of visual processing in the (circum)striate visual cortex, we examined the effect of single pulse transcranial magnetic stimulation over the occipital pole of healthy subjects who were engaged in a forced-choice visual letter identification task. Single letters, subtending a visual angle of 0.35 degrees, were foveally presented for 10 ms and were immediately followed by a mask. We investigated 30 different delays (d), defined as the time between the onset of the visual stimulus and the onset of the magnetic stimulus, from d = -100 ms to d = +190 ms, and 4 different midsagittal coil positions (x), defined as the distance between the lower edge of the coil and the upper edge of the inion, from x = 1 cm to x = 7 cm. Three out of four subjects showed three distinct delay intervals (dips) at which application of TMS resulted in an impairment of the task. The first dip was centred around d = -50 ms and occurred independently of the coil position; the second dip was centred around d = 0 ms and was elicitable only with the two lowest coil positions; the third dip was centred around d = 100 ms and was also elicitable only with the lower coil positions. In the fourth subject, only the first and the third dip were found. We conclude that there are two distinct periods when the activity in the (circum)striate visual cortex is necessary for the identification of visually presented letters.